Pembuatan Mi Basah Dari Tepung Fermentasi Singkong Untuk Siswa Planet Nufo, Desa Mlagen Rembang - Rohadi Rohadi; Bambang Tutuko (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The community service activity aims to provide knowledge and skills in producing instant fresh noodle made from cassava fermented flour and natural colorant from pea (Clitoria ternatea) flower extract for Planet Nufo students, Mlagen village, Rembang Regency. Plant Nufo’s curriculum integrates academic education at the level of Junior High School with the agriculture and animal husbandry sector.  The activity was held on Tuesday, May 24, 2022 attended by 20 students. The training material (theory) was delivered by authors using the lecture method, taking place in the Campus Hall, while the practice of making noodles done in the school’s production room provide by authors, assisted by two students. The result showed that giving theory is able to increase participants’ knowledge. However it is less effective with an extension effectiveness value (EP) of 11 percent. While practice provides real experience and skills to participants. The monitoring that carried out a week after work by interviewing the participants and supervisors methods showed community service activity was very useful. Participants have been able to produce fermented cassava flour with good results. Participants were also able to repeat the making of noodles by utilizing the materials and equipment with good product